Effect of Grading on Differences Using Mixed Concrete Aggregate Rough and Fine Aggregate Concrete Compressive Strength of Natural - Yulfriwini YULFRIWINI (International Conference on Engineering and Technology Development (ICETD), 2014)
The use of concrete is widely used because of its superiority among other ze strong in press conditions and weak in tensile conditions, and also the structural elements of the most widely used in building, because the material is easy to obtain and easy to make or easy to do. In the first experiment with a mixture of coarse and fine aggregate gradation naturally obtained an average compressive strength of 88.61 kg / cm3. In a second experiment with a mixture of coarse aggregate and fine aggregate gradation modification of the natural gradations obtained an average compressive strength of 103.31 kg / cm3. In the third experiment with a mixture of coarse aggregate and fine aggregate gradation modification of 50% and 50% natural materials sand material origin Mount Sugih obtained an average compressive strength of 121.24 kg / cm3